Persepsi Mahasiswa terhadap Fenomena Kepo - Pranajaya Pranajaya (Lembaga Penelitian Universitas YARSI, 2018)
The purpose of this study is to examine perceptions of phenomenon ofKepo (Knowing every particular object) among university students. Inthis study participants were randomly given questionnaire. This research is research that uses descriptive quantitative. Using structured questionnaire, unstructured interview by the research data were collected from 115 respondents of university of YARSI. The study confirmed that most of students are known about Kepo.